Current research and technological developments on the Dead Sea scrolls - Parry, Donald W.; Ricks, Stephen David. (Studies on the Texts of the Desert of Judah, 1996)
This volume of conference papers presents new discoveries, updated information, and technological advances in the study of the Dead Sea Scrolls. Two papers examine the identity of the messiahs in 4Q246 and 4Q521. A thorough analysis of scribal markings in the Dead Sea texts is presented. Biblical studies include multiple literary editions of biblical texts, the book of Numbers at Qumran, and the appearance of the Tetragrammaton in 4QSamᵃ texts. The notions of judgment and salvation according to Sapiential Work A are thoroughly examined, and the relationship of the six Barki Nafshi texts is carefully considered. New developments in the field of Dead Sea Scrolls studies include the Dead Sea Scrolls Database and DNA studies on the scrolls themselves.